PENGARUH PENGGUNAAN MODEL KEPALA BERNOMOR TERHADAP KETERAMPILAN MENULIS TEKS PIDATO SISWA KELAS IX G SMP NEGERI 2 KOTA JAMBI TAHUN AJARAN 2017/2018 - Risky Gustaviana; Ade Rahima; Sujoko Sujoko (Universitas Batanghari Jambi, 2018)
Abstract: The purpose of this study is to describe the effect of the use of numbered head models to the writing skills of speech text of grade IX students SMP Negeri 2 Kota Jambi Academic Year 2017/2018. The type of research used is quantitative and analyzed descriptively. The population that becomes the unit of analysis is all students of class IX G SMP Negeri 2 Kota Jambi as many as 36 students. The study used total sampling. Data collection techniques were conducted with questionnaires and assignments. Based on the results of the analysis, obtained the average value of post-test that has been taught by using the head model numbered 81.25 very good while the average value of pre-test is 71.25 good. This is evidenced by hypothesis testing using t test, in testing the hypothesis obtained value t count sebessar 9.881 greater than the value of ttable with dk 35 of 2.042 which means Ha accepted. Based on the hypothesis test that the numbered head model can be used by the teacher in speech writing lesson.Keywords: Write, Speech Text, Numbered Head Models.